IQ and the wealth of nations - Lynn, Richard, 1930- (Human evolution, behavior, and intelligence., 2002)
Lynn and Vanhanen argue that a significant part of the gap between rich and poor countries is due to differences in national intelligence (national IQs). Based on an extensive survey of national IQ tests, the results of their study challenge the previous theories of economic development and provide a new basis to evaluate the prospects of economic development throughout the world.